Strategi Peningkatan Pendapatan Petani Udang Tambak Di Desa Kepuh Legundi - Malik Fajar Ramadlan; Pardiman Pardiman; Ita Athia (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract Strategy for Increasing the Income of Pond Shrimp Farmers in the village of kepuh legundi Shrimp pond cultivation, especially the Vaname type, is classified as a type of shrimp that has good business prospects to be developed, besides the potential for developing Vaname shrimp, it also has the potential as a shrimp export commodity that is able to provide foreign exchange from fishery products. Because vaname shrimp is a type of shrimp that has the ability to adapt to a low temperature environment.Even the cultivation of vaname shrimp using only a tarpaulin pond is a very good business to use as a cultivation business whose profit value is fantastic. Therefore, with this consideration, this is the reason for researchers to conduct research by taking the title Strategy for Increasing Pond Shrimp Farmers in Kepuh Legundi Village. This study aims to explain the most appropriate strategy that can be used by the company through analyzing the strengths and weaknesses, as well as the opportunities and threats faced by the Vaname Shrimp Farm CV.Arkhaq Putra in Gresik Regency, East Java Province.The results of Vaname pond shrimp cultivation, the results obtained from the harvest are Rp. 2,500,000, - Fixed costs are Rp. 28,000,000, - variable costs are Rp.1,159,870 -Total cost Rp.1,187,870,000,- Income Rp. 1.312.130.000, And through a SWOT analysis, the results of this study can be said: That from the results of IFAS and EFAS, the strength of the CV. Arkhaq Putra's strengths are 19.94 while weaknesses are 5.7 so the cells (quadrant) internal factors are 19.94 – 5.7 = 14.24 while the opportunities for this strategy are 17.08 with a threat of 10 being external cells (quadrants). factor, namely 17.08 – 10 = 7.08 which is in Cell (quadrant) 1 on the SWOT analysis diagram. In this effort, it shows that the marketing strategy is an aggressive strategy by using all strengths to take advantage of opportunities. This strategy is proven based on existing efforts, namely by using all strengths in taking advantage of opportunities. This strategy is a profitable strategy because the business has the opportunity and strength in advancing CV Shrimp Farms. Arkhak Putra. The SWOT matrix is carried out by entering all the Strenght, Weakness, Opportunity and Threats points into the matrix and then dividing it in four attempts by allocating the results of the multiplication of weights and ratings into SO, WO, ST, and WT strategies which are a combination of all strengths, weaknesses, opportunities. and threats faced by CV.Arkhq Putra's Shrimp Pond Busines. Keywords : Strategy for Increasing the Income of Pond Shrimp Farmers in the village of kepuh legundi